Highly Hydrophilic Electrospun Polyacrylonitrile/ Polyvinypyrro-lidone Nanofibers Incorporated with Gentamicin as Filter Medium for Dam Water and Wastewater Treatment - R. Alharbi, Abdulaziz; M. Alarifi, Ibrahim; S. Khan, Waseem; Asmatulu, Ramazan (Journal of Membrane and Separation Technology, 2016)
The need for advancement in filtration technology has spurred attention to advanced materials, such as electrospun nanofiber membranes, for providing clean water at a low cost with minimum initial investment. Polymer nanofibers can be fabricated by using different techniques, such as template synthesis, self-assembly, drawing, phase separation, and electrospinning. Due to its distinctive properties, electrospinning has become a method of choice for fabricating nanofiber membranes quickly with minimal investment. In this study, polyacrylonitrile (PAN) was dissolved in dimethylformamide (DMF), and different weight percentages of polyvinylpyrrolidone (PVP) and gentamicin sulfate powder were added to the solution to fabricate nanomembranes via the electrospinning process. Gentamicin was added to remove bacteria and viruses and prevent fouling, while PVP was added to make the surface of the membrane hydrophilic for enhancing the filtration rate and efficiency. Two water samples were chosen for the filtration processes: dam water and city wastewater. For the dam water sample, PH, turbidity, TDS, Ca++, Mg++, sulfates, nitrates, fluoride, chloride, alkalinity and silica were reduced to +3.64%, 89.6%, 6.52%, 10.5%, 9.96%, 5.16%, 17%, 19.5%, 6.63%, 1.43% and 63.5% respectively. The total coliforms and E. coli content were reduced to 4.1 MPN/100ml and 0 MPN/100ml, respectively with PAN containing 10 wt. % PVP and 5 wt. % Gentamicin. For wastewater sample, PH, turbidity, TDS, TSS, BODs, phosphate, ammonia, oil-greases and DO were reduced to + 3.62%, 79%, 6.33%, 84%, 68%, 1.70%, 15.8%, 0% and 6% respectively. The total coliforms and E. coli content were also lowered to 980 MPN/100ml and 1119.9 MPN/100ml, respectively with PAN containing 10 wt. % PVP and 5 wt. % Gentamicin. The morphology and dimensions of the nanofibers were observed using a scanning electron microscope (SEM). Both SEM and microscopic images of the nanomembrane before and after filtration proved that electrospun PAN nanofibers have superior water filtration performance.